ナンキョク チメイ メイメイ ニツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 国立科学博物館極地研究センター; コクリツカガクハクブツカンキョクチケンキュウセンター; Polar Research Center National Science Museum (国立極地研究所, 1972)
P(論文) On 1 December, 1971 the Antarctic Place-names Committee of Japan was organized as an advisory committee to the Director of the Polar Research Center, National Science Museum. The members of the Committee are as follows : Dr. Torao YOSHIKAWA, Chairman, University of Tokyo Dr. Yoshimichi HARADA, Co-chairman, Geographical Survey Institute Mr. Takakiyo OTSUKA, Ministry of Education Dr. Kou KUSUNOKI, Polar Research Center Mr. Satoshi SHIGEHIRO, Hydrographic Division, Maritime Safety Agency Mr. Koichi TSUTSUMI, Ministry of Foreign Affairs Dr. Takao HOSHIAI, Polar Research Center Dr. Kazuo MURAOKA, Geographical Survey Institute Mr. Nozomi MURAKOSHI, Polar Research Center Mr. Kotaro MORITA, Japan Meteorological Agency Mr. Keiichiro YAMAGUCHI, Geographical Survey Institute Mr. Yoshio YOSHIDA, Hiroshima University Mr. Masaaki WASHIO, National Science Museum Mr. Ryuzo WATANABE, Hydrographical Division, Maritime Safety Agency. The Committee worked out 47 new place names, which were officially approved by the Japanese Antarctic Research Expedition Headquarters, under date of 22 June, 1972. An alphabetical list records newly adopted 47 names, in addition to previously adopted 98 names. departmental bulletin paper